Structured input and structured output on the acquisition of English passive constructions: A self-paced reading study measuring accuracy, response and reading time. (November 2022) - Benati, Alessandro
Abstract: This study investigates the relative effects of structured input and structured output on the acquisition of English passive construction forms. This investigation builds upon the work carried out within the structured input research framework with the intention to measure online effects of structured input utilising a self-paced reading test. The self-paced reading test is a reliable measurement of language processing. Fifty-three Chinese (L1) subjects participated in the current study. They were all learning English in a university in the United Kingdom. A randomization procedure was adopted to assign subjects to the two instructional groups: structured input ( n  = 29); structured output ( n  = 24). None of the instructional treatments included explicit information. Pre-tests and post-tests were administered before and after the end of instructional treatment which lasted for 2 h over a two-day period. The main findings from this experimental study confirmed the positive effects of structured input in facilitating the intake of passive constructions in English via correct parsing. The structured output group that did not improve between pre and post-tests. The present study contributes to the debate for more empirical research to investigate the role of pedagogical interventions using online tests to measure accuracy of response, response and reading time.